Self-Awareness Mechanism for Top-down Attention using Fuzzy Logic in Sustainable Business Intelligence - Muhammad Furqan Khan; Wasim Ahmad Khan; Muhammad Muzaffar Hameed; Arslan Ahmad Siddiqi (Sustainable Business and Society in Emerging Economies)
Purpose: The self-awareness mechanism can serve as inspiration for the design of an artificial intelligence system for top-down attention, for which self-awareness plays an indispensable role. When agents receive multiple stimuli from the environment, it becomes very difficult for them to focus solely on the most important stimulus. So, a self-awareness mechanism is required to regulate attention.